A theoretical analysis of the ternary hybrid nanofluid flows over a non-isothermal and non-isosolutal multiple geometries. Issue 4 (April 2023) - Ramzan, Muhammad; Kumam, Poom; Lone, Showkat Ahmad; Seangwattana, Thidaporn; Saeed, Anwar; Galal, Ahmed M.
Abstract: The current problem is concerned with the study of magnetohydrodynamic ternary hybrid nanofluid flow over two distinct geometries i.e., cone and wedge. The ternary hybrid nanoliquid with MHD has a lot of engineering and industrial applications. In polymer data processing, cone and wedge geometries are frequently utilized. Therefore, the present problem is designed to the flow of ternary hybrid nanoliquid over multiple geometries. Hybrid nanoliquids performed well in the heat transport rate as compared to the nanoliquid and conventional liquid. Here in this study, the idea of ternary hybrid nanoliquid is introduced to improve the energy and mass transmissions which show more satisfactory results in the thermal and mass transmission performance. The impacts of chemical reaction and thermal radiation are also executed in this model. The formulation of the present study is performed in the form of PDEs which are then transformed into the ODEs by using suitable similarity transformations. The homotopic analysis scheme is implemented for the semi-analytical solution of the existing model. Some major results that materialize from the present simplification are that; the tri-hybrid nanoliquid velocity is greater for the rising nanoparticles volume fractions. The enlargement in radiation parameter enlarged the tri-hybrid nanoliquid thermal profile. The mass transfer rate of the ternary hybrid nanoliquid is lesser for the Schmidt number and chemical reaction. Intensification in nanoparticles volume fractions and radiation parameter has increased the ternary hybrid nanofluid heat rate transfer for both cone and wedge geometries.